2005
DOI: 10.1021/la050988g
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl Guar−Borate Interactions with Tear Film Mucin and Lysozyme

Abstract: The interactions of hydroxypropyl guar (HPG) with boric acid, lysozyme, and mucin were characterized by rheology, light scattering, electrophoresis, and isothermal titration calorimetry to help understand how HPG interacts with tear film components. Borate binds to guar under pH, temperature, and ionic strength conditions representative of those found in the eye. The HPG-borate complexes behave as anionic polyelectrolytes and thus interact with cationic lysozyme, a major tear film protein, whereas HPG-borate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…[60] However, the majority of studies evaluating mucoadhesive interactions have reported the use of commercially-available lyophilized porcine gastric mucin [51,57,58,[61][62][63][64] and bovine submaxillary gland mucin. [17,[65][66][67] Although, these products may differ from the native mucins they often show less batch-to-batch variability and give more reproducible results.…”
Section: Methods To Study Mucoadhesive Interactionsmentioning
confidence: 99%
“…[60] However, the majority of studies evaluating mucoadhesive interactions have reported the use of commercially-available lyophilized porcine gastric mucin [51,57,58,[61][62][63][64] and bovine submaxillary gland mucin. [17,[65][66][67] Although, these products may differ from the native mucins they often show less batch-to-batch variability and give more reproducible results.…”
Section: Methods To Study Mucoadhesive Interactionsmentioning
confidence: 99%
“…It has better water solubility and film forming property than guar gum (Lu et al 2005;Xiao et al 2003) and plays a large role in the various products of chemically modified guar gum (Cheng et al 2002). HPG has been widely used in many industries such as oil recovery, food industry, paints and the formulation of cartridge explosives (Wu et al 2010;Xiao et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the dynamic transition between B(OH) 4 − and B(OH) 3 upon the pH variation: B(OH) 4 − is an effective crosslinking agent for GG, while B(OH) 3 is not; B(OH) 4 − was converted to B(OH) 3 upon the addition of a HCl solution, causing the disintegration of hydrogels; conversely, with the addition of NaOH, B(OH) 4 − was formed, thus, the hydrogels were recovered. Lu et al 28 reported in their study of hydroxypropyl guar (HPG)-borate interactions that the interactions between HPG and borate was sensitive to pH. The sol-gel transition also occurred during the heating/cooling process: the hydrogel became liquid when heated to 70 °C, while the hydrogel was re-formed after cooled down to 20 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%